Conflicting signals in phylogenetic relationships and taxonomy of Anatolian endemic Silene sordida (Caryophyllaceae) - Toprak, Zeynep; Yildiz, Kemal (Phytotaxa, 2022)
Silene sordida is a Southwest Anatolian endemic that shows highly contradicting signals regarding its actual classification. Using morphological, molecular, and palynological data we here investigate phylogeny and taxonomy of S. sordida. Morphological and palynological features of S. sordida are compared to the species known as very closely related to S. sordida. In addition, we generated DNA sequences of three nuclear and one plastid loci from S. sordida and some allied species belonging to several sections and analyzed these data together with the available sequence data of corresponding taxa. Our findings strongly support the unrelatedness of S. sordida with the section Atocion. The relationship between S. sordida and the section Cryptoneurae and S. odontopetala remains unstable among the four loci analyzed. Both morphological and molecular evidence suggest the recognition of a new monotypic section (here named “Sordidae”).